A Carbon Flux Assessment Driven by Environmental Factors Over the Tibetan Plateau and Various Permafrost Regions. Issue 5 (3rd May 2019) - Lin, Shan; Wang, Genxu; Feng, Jinming; Dan, Li; Sun, Xiangyang; Hu, Zhaoyong; Chen, Xiaopeng; Xiao, Xiao
Abstract: In this study, the spatiotemporal changes in net primary production (NPP) and drivers, including climate change, atmospheric CO2 concentration and land use change, over the Tibetan Plateau from 1979 to 2016 were investigated using the version 4.5 of the Community Land Model. Based on high‐resolution atmospheric forcing data, six numerical experiments were designed to assess the relative contribution of different environmental factors on NPP. Our simulation results suggest that NPP over the Tibetan Plateau has increased significantly at a rate of 2.25 Tg C/year 2 since 1979. At the plateau scale, changes in precipitation, CO2 concentration, and land use change contributed approximately 63.3%, 16.7%, and 9.5% to the interannual variation of NPP, respectively. Temperature did not exert a significant effect on the trends of NPP, which results from the increasing temperature enhancing the autotrophic respiration (AR) more than the gross primary production. We also divided the alpine grasslands into four types, including alpine meadow of permafrost, alpine steppe of permafrost, alpine meadow of seasonal frost, and alpine steppe of seasonal frost. We found that the increasing rate of NPP in permafrost regions was significantly higher than that in seasonal frost regions. Compared with other factors, precipitation change played a dominant role in the NPP over the four different types of grasslands. Temperature‐induced change on NPP and AR was larger in the alpine meadow regions compared to in the alpine steppe regions. In addition, NPP and AR showed a more remarkable response to temperature change over alpine meadow of permafrost than other regions. Key Points: We identify the main factors leading the change of net primary production and their regional difference over the Tibetan Plateau We indicate the differences in net primary production changes and driving factors over different permafrost regions Change in precipitation played a dominant role in the increase of net primary production over plateau scale and different permafrost regions